2020
DOI: 10.7759/cureus.11968
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Cochlear Implant: Results in Saudi Children

Abstract: Objective To assess the quality of life (QoL) in Saudi children with cochlear implants (CI) and determine sociodemographic and clinical factors that have an impact on the perceived QoL. Methods A cross-sectional study is performed by comparing the QoL of Saudi toddlers and young CI recipients with normal children, using the Paediatric Quality of Life Inventory 4.0 - Generic core scale (PedsQL TM 4.0 - GCS). A self-administered questionnaire was sent to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…Additionally, one study in Brazil found a significant correlation between mother’s level of education, but not father’s, and some domains of QoL after cochlear implantation [ 22 ]. In contrast, the level of education of both mother and father was not associated with the QOL in another study of Saudi children [ 20 ]. It is optimistic to find that the outcome in our study is not related to the income of the family which is consistent with other studies [ 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one study in Brazil found a significant correlation between mother’s level of education, but not father’s, and some domains of QoL after cochlear implantation [ 22 ]. In contrast, the level of education of both mother and father was not associated with the QOL in another study of Saudi children [ 20 ]. It is optimistic to find that the outcome in our study is not related to the income of the family which is consistent with other studies [ 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…12,23 Regarding associated factors of QoL among children with CI, our finding is consistent with the previous studies in which age of CI is significantly correlated with QoL of children. 14,21,22,24 It has been reported that children who had earlier exposure to sounds (especially those who underwent implantation by 3.5 years of age) have better opportunities for age-appropriate auditory development, normal development of central auditory pathways, resulting in they were more integrated and involved with the surroundings and less likely to feel isolated and left behind. 25 In addition, the present study also found that duration of CI use showed positive correlation with QoL of the children.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that there are significant differences in rating QoL between children-self-reported and parental proxy. 14 Therefore, the results may be influenced by different point of views. Previous studies confirmed the effectiveness of CI in improving QoL among children, and the benefits appear to keep stable over the years.…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations